Science behind children’s handwashing: action study of 9- to 10-years-old elementary school students in Japan - Oura, Asae; Naito, Yukiko; Yako-Suketomo, Hiroko; Nakata, Kei; Koyama, Masayuki; Ohnishi, Hirofumi (Frontiers in Public Health, 2024)
Background: Hand washing instructions for children have been implemented in school education to establish good lifestyle habits. However, repeated hand washing through education from early childhood was common for both teachers and children. If this continues, children might assume they already know how to wash their hands, stop taking handwashing instructions seriously, and become increasingly lax about washing their hands. Purpose: This study aimed to develop a new handwashing education method for children. Methods: We applied the adenosine triphosphate (ATP) test to health education on hand washing in elementary schools. This study was conducted as part of a class for elementary school students in October 2023, in Hokkaido, Japan. The subjects were 157 third-grade (9-10 years old) elementary school students. After excluding absent pupils, 147 were included in the analysis. Results: Both pre- and post-education, ATP values after handwashing were lower than those before handwashing. Following the education, children's handwashing behavior improved, with an increase in the number of point washed and appropriate timing of handwashing. Conclusion: The new handwashing education program utilizing the ATP-test succeeded in promoting handwashing behavior among many children. Visualizing handwashing using ATP values was effective in motivating children.